CRITICAL REVIEW OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN ISLAMIC RELIGIOUS EDUCATION IN EARLY CHILDHOOD EDUCATION (PAUD) - Shaliadi, Ikrom; Ludfi, Ludfi (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to critically analyze the implementation of the Independent Curriculum in Early Childhood Education (PAUD) with a focus on the integration of Islamic Religious Education (PAI), identify challenges and opportunities for its implementation, and provide recommendations for PAI integration strategies that are contextual, creative, and in line with the spirit of independent learning. The method used is a literature study with a qualitative descriptive approach, utilizing literature from scientific journals, books, research reports, and policy documents. The results of the study indicate that the Independent Curriculum opens up space for PAI integration through thematic, project-based, and fun learning, which supports the formation of Islamic character as well as 21st-century competencies. Challenges faced include limited teacher competency, infrastructure readiness, and suboptimal policy support, while opportunities lie in curriculum flexibility, a holistic approach, and parental involvement. This study recommends project-based, creative, contextual PAI integration strategies, as well as strengthening teacher training and collaboration with parents to support successful implementation. These findings are expected to serve as a reference for teachers, schools, and policymakers in optimizing PAI integration in PAUD in an adaptive and meaningful manner.